OPTIMASI DAN FORMULASI EKSTRAK ETANOL UMBI WORTEL (Daucus carota L.) SEBAGAI FACE SERUM SEBAGAI FACE SERUM [OPTIMIZATION AND FORMULATION OF CARROT ETHANOL EXTRACT (Daucus carota L.) AS A FACE SERUM] - Karnelasatri, Karnelasatri; Trisina, Jessica; Purba, Rossa Maranatha (Universitas Pelita Harapan, 2023)
Carrot bulbs are known to contain secondary metabolite compounds that can act as antibacterials due to their activity, which suppresses the synthesis of nucleic acid, cytoplasmic membrane function, and energy metabolism in bacteria. This research was carried out using laboratory experimental methods through the determination of the plant, production of simplicia, extraction by ethanol (96% as solvent) with the maceration method, phytochemical screening, antibacterial assay, optimization of the base formula, formulation of carrot extract, physical evaluation of the products, and hedonic testing. The yield of 96% ethanol extract of the carrot bulbs was 53.29%, and the water content of the extract was 16.14%. Furthermore, the antibacterial activity of the extract (500.000 ppm) against Staphylococcus aureus showed an inhibitory zone of 5.1 ± 3.42 mm. The carrot extract serum formulas F1, F2, and F3 meet the organoleptic and homogeneity criteria; however, the F2 formula does not meet the pH and viscosity criteria. Based on the hedonic statistical test, no significant difference was found in each formula; nevertheless, based on the average value of the respondents, it was known that the F1 formula had the highest preference.Bahasa Indonesia Abstract:Umbi wortel dapat berperan sebagai antibakteri karena mengandung senyawa metabolit sekunder yang dapat menekan sintesis asam nukleat, fungsi membran sitoplasma, dan metabolisme energi pada bakteri. Penelitian ini dilakukan dengan metode eksperimental laboratorium yang dilakukan dengan determinasi tumbuhan, pembuatan simplisia serta ekstraksi dengan pelarut etanol 96% dengan metode maserasi, skrining fitokimia, uji antibakteri ekstrak, optimasi basis sediaan, formulasi sediaan, evaluasi fisik sediaan, dan uji hedonik sediaan. Rendemen ekstrak etanol 96% umbi wortel yang diperoleh adalah sebesar 53,29% dan kadar air ekstrak adalah 16,14%. Aktivitas antibakteri dari ekstrak (500.000 ppm) terhadap Staphylococcus aureus menunjukan zona hambat sebesar 5,9 ± 0,49 mm. Sediaan serum ekstrak umbi wortel F1, F2, dan F3 memenuhi syarat organolepik dan homogenitas, namun sediaan F2 tidak memenuhi syarat pH dan viskositas sediaan. Berdasarkan uji statistik hedonik sediaan, tidak ditemukan perbedaan signifikan pada tiap sediaan, namun berdasarkan nilai rata-rata responden diketahui bahwa sedian F1 menjadi preferensi tertinggi.